Development of an artificial metalloenzyme from a nicotinamide-dependent enzymatic scaffold - Basle, Mattias Pascal Fabien (2020)
Transfer hydrogenation reactions can yield a diverse range of chiral products to be used as such, or as building block for the synthesis of more complex molecules. Biocatalysts and artificial metalloenzymes (ArMs) are sustainable alternatives to chemical routes. ArMs are the result of the insertion of a metal ion or complex into a biological scaffold. Most of the ArMs use proteins as a biological hosts to provide a highly functionalised environment where reactants are brought together and activated in very specific ways. The incorporation of the metal catalyst provides a synthetic activity, not necessarily accessible by natural biocatalysts. Most of the ArMs are based on nonenzymatic scaffolds, containing large binding sites generally evolved to accommodate hydrophobic molecules. As such, their design requires efforts to improve the specific chemical reaction targeted. Here we present the development of new ArMs that could be used as a biocatalytic platform for transfer hydrogenation reactions. In previous work, our group generated an artificial mutant of Thermoanaerobacter brockii alcohol dehydrogenase (TbADH) by bioconjugation of a piano-stool rhodium catalyst to cysteine 37 in the active site. In the present work, a computational design approach was used to investigate more suitable positions for the catalyst to be anchored within the catalytic site of the enzyme, using a covalent anchoring strategy. Four positions were found where thiol sidechains would be more accessible than the reported labelled position 37. Single cysteine mutations were prepared at those positions and compared with two other protein variants, where all but one native cysteine residues in the binding pocket were removed. After optimisation of the bioconjugation process with three different ligands bearing a bidentate N-N motif, two enzymatic scaffolds were identified and used for the development of ArMs, using covalent anchoring of Rh and Ir complexes. Five different ArMs were subsequently created and their activity towards the regeneration of nicotinamide cofactors and derivatives was assessed. One mutant bearing a rhodium complex bound at position 243 showed catalytic activity for the reduction of nicotinamides, with a discrimination between the natural cofactors and their mimics. This ArM could potentially be used in a cofactor recycling system compatible with both nicotinamide cofactors. Whilst some of the ArMs suffered from the dissociation of the Cp*Rh functionality from its complex, resulting in unspecific binding and catalysis, one of the constructs, possessing a Cp*Rh(bipyridine) catalyst, showed very promising results for the recycling of NADPH and of benzyl nicotinamide. Besides a covalent anchoring approach, which requires tedious work for the development of ArMs, a supramolecular approach was also investigated, by taking advantage of one feature of ADH, their nicotinamide binding pocket. Benzyl nicotinamide derivatives were synthesised and their capacity to interact with two ADHs, in a similar fashion to their natural cofactor, was assessed with the aim of using these as anchors for synthetic metal catalysts into ADHs. The lack of interactions observed with both enzymes, TbADH and horse liver alcohol dehydrogenase (HLADH), suggested that more hydrophilic structures would be required to yield a suitable supramolecular anchor. To provide initial data for further investigation on the development of ArMs by supramolecular anchoring with ADH enzymatic scaffolds, two separate studies were performed in silico. The first one focused on the anchor structure and its capability to mimic interactions within the cofactor binding site and led to the design of three potential supramolecular anchors where the benzyl substituent was replaced with more hydrophilic functionalities. The second study focused on finding enzymatic scaffolds capable of accommodating the hydrophobic benzyl nicotinamide derivatives. This study led to three potential ADH candidates. To assess the validity of the computational models from the 2 studies, experimental work will be required.